The impact of physical exercise on adolescents’ mobile phone dependency: the serial mediating role of self-esteem and depression - Jingtao Wu; Yanhong Shao; Wanli Zang (Frontiers in Psychology)
ObjectiveThe objective of this study is to examine the impact of physical exercise on the prevalence of mobile phone dependency among middle school students, as well as to delineate the serial mediating roles of self-esteem and depression within this relationship.MethodsA convenient cluster random sampling method was employed to conduct a questionnaire survey among 3,786 middle school students from Guangdong, Sichuan, Zhejiang, Henan, and other provinces. Measurements were taken using the Physical Activity Rating Scale (PARS-3), the Self-esteem Scale, the Depression Scale, and the Mobile Phone Dependency Scale.ResultsPhysical exercise was significantly negatively correlated with mobile phone dependency (r = −0.400, p < 0.001) and depression (r = −0.400, p < 0.001), and positively correlated with self-esteem (r = 0.257, p < 0.001). Mobile phone dependency was significantly positively correlated with depression (r = 0.540, p < 0.001) and negatively correlated with self-esteem (r = −0.129, p < 0.001). Depression was negatively correlated with self-esteem (r = −0.396, p < 0.001). Mediation analysis revealed that self-esteem and depression significantly mediated the relationship between physical exercise and mobile phone dependency, with a total indirect effect of −0.116 (95% CI = [−0.239, −0.140]), accounting for 100% of the total effect. Specifically, the indirect effect through “physical exercise influencing depression, which then affects mobile phone dependency” was −0.076 (95% CI = [−0.224, −0.128]), accounting for 65.52% of the total effect; the indirect effect through “physical exercise influencing self-esteem, which then influences depression, and in turn affects mobile phone dependency” was −0.040 (95% CI = [−0.063, −0.027]), accounting for 34.48%; the indirect effect through “physical exercise influencing self-esteem, which then affects mobile phone dependency” was not significant (95% CI included 0).ConclusionPhysical exercise can directly reduce the dependency of middle school students on mobile phones, and it can also indirectly reduce mobile phone dependency by enhancing self-esteem and reducing levels of depression.